Efeitos da Passiflora incarnata e do midazolam no controle da ansiedade em pacientes submetidos à exodontia de terceiros molares inclusos - Dantas, Liliane Poconé (2014)
Anxiety symptoms are frequently observed at the dental office, from the simpler to more invasive procedures, such as surgery. The aim of this research was to compare the Passiflora incarnata and the midazolam effects for the anxiety control in patients undergoing to mandibular third molars extraction. 40 volunteers underwent a bilateral extraction of mandibular third molars in a clinical trial, randomized, controlled, double-blind and crossover. All dental units were asymptomatic, at similar positions and surgical levels. Passiflora incarnata 260 mg or Midazolam 15 mg were orally administered, 30 minutes before surgery. In both cases was administered a single intramuscular dose of dexamethasone 8 mg, 30 minutes before surgery as a prevention of hyperalgesia and edema control. The anxiety level evaluation was made by using questionnaires and physical parameters (heart rate (HR), blood pressure (BP) and the oxygen saturation level (SpO2)). It was classified at three distinct phases: Phase I (baseline), Phase II (surgical intervention) and Phase III (return consultation). There were no significant differences between the protocols on BP, HR and SpO2 considering each procedure independently. Over 70 % of volunteers responded feel quiet or a little anxious, with both medications. With Midazolam, 20% of subjects reported not remember anything at all, while the Passiflora showed little or no ability to interfere in memory at all. Among the adverse effects, somnolence was the most commonly reported effect for the two protocols, 82.5% when administered Midazolam and 50% with Passiflora. However, there was no significant statistically differences between protocols for these effects. So the Passiflora incarnata showed a similar anxiolytic effect to midazolam, being safe and effective conscious sedation in adult patients underwent extraction of mandibular third molars.